Design and construction of a localized surface plasmon resonance based gold nanobiosensor for rapid detection of brucellosis - Vakili, Sina; Asadikaram, Gholamerza; Torkzadeh-Mahani, Masoud; Behroozikhah, Alimohammad; Nematollahi, Mohammad Hadi; Savardashtaki, Amir (Kuwait Journal of Science, 2021)
In this study, a localized surface plasmon resonance (LSPR) nanobiosensor was designed to quantify anti-Brucella antibody in the human sera. Smooth Lipopolysaccharide (LPS) was extracted from Brucella melitensis via modified hot phenol water method and fixed on the surface of the gold nanoparticles by covalent interactions. In order to obtain the best performance from the designed probe, the ratio of LPS to gold nanoparticle was optimized. Dynamic light scattering was used for characterization of the probe. The reduction of the LSPR peak at 600 nm was used to quantify the amount of captured anti-Brucella antibody. Finally, satisfactory results were obtained when the nanobiosensor was used to analyze the control and patient sera for the presence of anti-Brucella antibodies.